Structure-property relationship in charge transporting behaviour of room temperature liquid crystalline perylenebisimides - Prajitha, K. P.; Chithiravel, Sundaresan; Krishnamoorthy, K.; Asha, S. K. (Journal of Materials Chemistry C, 2014)
A homologous series of pentadecyl phenol functionalized perylenebisimide (PBI) terminated with trialkoxy gallate esters was synthesized, where the terminal alkyl chain length was varied from n = 4 to 12 (PBI-En). The thermotropic liquid crystalline (LC) characteristics of the molecules were analyzed using differential scanning calorimetry (DSC), polarized light microscopy (PLM) combined with variable temperature wide angle X-ray diffraction (WXRD) techniques. A clear odd-even oscillation was observed in the melting as well as isotropization enthalpies as a function of alkyl spacer length in the terminal gallate unit, with the even spacers exhibiting higher values. The higher members of the series with n > 8 exhibited thermotropic liquid crystalline textures in the PLM, which remained stable until room temperature. The nature of the LC phase was identified to be columnar rectangular and columnar hexagonal based on detailed analysis of the WXRD pattern recorded in the LC phase. The WXRD pattern of the room temperature LC frozen samples indicated a nearly constant intra columnar stack distance of similar to 3.7 angstrom for all the members. The space-charge-limited current (SCLC) values of the LC frozen sample films were analyzed for dependence of the bulk mobility estimate on the nature of the LC phase. The columnar hexagonal phase exhibited a mobility value one order (10(-3) cm(2) V-1 s(-1)) higher than that of crystalline (10(-4) cm(2) V-1 s(-1)) and two orders higher than that of columnar rectangular phase (10(-5) cm(2) V-1 s(-1)), indicating a strong dependence of packing on bulk mobility.

Detailed study on the thermal, photo-physical and electrochemical properties and OFET applications of D-pi-A-pi-D structured unsymmetrical diketopyrrolopyrrole materials - Bharath, D.; Chithiravel, Sundaresan; Sasikumar, M.; Chereddy, Narendra Reddy; Shanigaram, Balaiah; Bhanuprakash, K.; Krishnamoorthy, K.; Rao, V. Jayathirtha (RSC Advances, 2015)
A series of seven unsymmetrical diketopyrrolopyrrole (DPP) derivatives with donor-pi-acceptor-pi-donor (D-pi-A-pi-D) architecture have been designed, synthesized and well characterised. The effect of the electron donating capacity and extent of electronic conjugation of the end-capping units on the thermal, photo-physical and electrochemical properties of the synthesized materials was thoroughly investigated using various experimental techniques and theoretical calculations. Organic field-effect transistors (OFETs) were fabricated using these materials to obtain their hole/electron transporting characteristics. All these materials showed moderate to good hole transporting ability, and the OFET fabricated using the DPP-derivative with benzofuran and pyrene end groups exhibited a hole mobility of 6.7 x 10(-4) cm(2) V-1 s(-1) with VT of similar to 9 V. The observed photo-physical, electrochemical, thermal, and charge carrier properties of the synthesized DPP-derivatives indicated their applicability in various areas like organic photovoltaics, disposable electronics and biomedical devices.

Seeded on-surface supramolecular growth for large area conductive donor-acceptor assembly - Goudappagouda; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Gosavi, Suresh W.; Babu, Sukumaran Santhosh (Chemical Communications, 2015)
Charge transport features of organic semiconductor assemblies are of paramount importance. However, large-area extended supramolecular structures of donor-acceptor combinations with controlled self-assembly pathways are hardly accessible. In this context, as a representative example, seeded on-surface supramolecular growth of tetrathiafulvalene and tetracyano-p-quinodimethane (TTF-TCNQ) using active termini of solution-formed sheaves has been introduced to form an extended assembly. We demonstrate for the first time, the creation of a large-area donor-acceptor assembly on the surface, which is practically very tedious, using a seeded, evaporation-assisted growth process. The excellent molecular ordering in this assembly is substantiated by its good electrical conductivity (similar to 10(-2) S cm(-1)). The on-surface assembly via both internally formed and externally added sheaf-like seeds open new pathways in supramolecular chemistry and device applications.

Alkyl-chain-separated triphenybenzene - carbazole conjugates and their derived polymers: candidates for sensory, electrical and optical materials - Kaleeswaran, D.; Vishnoi, Pratap; Kumar, Subramani; Chithiravel, Sundaresan; Walawalkar, Mrinalini G.; Krishnamoorthy, Kothandam; Murugavel, Ramaswamy (Chemistry Select, 2016)
Four new triphenylbenzene based carbazoles (THPBCz4, THPBCz6, THPBCz8 and THPBCz10) and polycarbazoles (polyTHPBCz4, polyTHPBCz6, polyTHPBCz8 and polyTHPBCz10), have been synthesized. Photoluminescence spectra of the monomers in dichloromethane exhibit two intense bands at 353 and 369 nm. Two additional bands (410 and 435 nm) are also observed due to intermolecular interactions. These bands are more intense in the case of thin films, indicating stronger pp stacking interactions in the solid state. Due to the extended p-conjugation, the polycarbazoles display two main emission bands (495 and 520 nm) which are red shifted as compared to the monocarbazoles. Due to the presence of emissive platforms such as triarylbenzene and carbazole, both monomers and polymers, function as efficient sensors for the detection of polynitroaromatic analytes (PA, DNT, rho-DNB and m-DNB). The electrochemically polymerized carbazole derivatives showed maximum capacitance of 41 F/g for polyTHPBCz6. The SCLC measurement reveals a maximum mobility of 6 x 10(-6) cm(2)/Vs for polyTHPBCz4 that showed better packing due to flexible alkyl chains that connect the conjugated moieties.

Copolymers comprising monomers with various dipole and quadrupole as active material in organic field effect transistors - Singh, Saumya; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam (Journal of Physical Chemistry C, 2016)
Copolymers of 4,4-difluoro-4-borata-3a-azonia-4a-aza-s-indacene (BODIPY) and diketopyrrolopyrrole (DPP) were synthesized. The BODIPY has a permanent dipole and the DPP has a quadrupole. The dipole and the quadrupole in the monomers are expected to bring the polymers closer and to improve the charge-transport properties. By judicious choice of these monomers, the electron wave function is evenly distributed through the molecules. However, we notice that the torsional angle at the connecting point of BODIPY and DPP is a function of the methyl moieties at the beta,beta' position of the BODIPY. We found that the polymer comprising DPP and BODIPY without methyl moiety at beta,beta' position showed a torsional angle of 27, the lowest among the three polymers studied in this work. The absorption spectrum of the polymer showed transitions because of vibronic coupling indicating linearity along the polymer backbone. The band gap of the polymer was found to be 1.2 eV. The thermally stable polymer showed an ambipolar charge transport of 0.01 cm(2)/(V s).

Nitrogen doping in oxygen-deficient Ca2Fe2O5: a strategy for efficient oxygen reduction oxide catalysts - Jijil, Chamundi P.; Lokanathan, Moorthi; Chithiravel, Sundaresan; Nayak, Chandrani; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Babu, P. D.; Kakade, Bhalchandra A.; Devi, R. Nandini (ACS Applied Materials and Interfaces, 2016)

P4VP and oligo(phenylenevinylene)-perylenebisimide mixed donor-acceptor supramolecular comb polymer complexes with improved charge carrier mobility - Saibal, B.; Chithiravel, Sundaresan; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Random donor-acceptor (D-A) supramolecular comb polymers were formed when hydroxyl functionalized donor and acceptor small molecules based on Oligo(phenylenevinylene) (named OPVCN-OH) and Perylenebisimide (named UPBI-PDP), respectively, were complexed with Poly(4-vinyl pyridine) (P4VP). A series of random D-A supramolecular comb polymers were formed by varying the ratios of UPBI-PDP and OPVCN-OH with P4VP. A 100% P4VP-donor polymer complex [P4VP(OPV1.00)] and a 100% P4VP-acceptor polymer complex [P4VP(UPBI1.00)] were also synthesized and characterized. Complex formation was confirmed by FT-IR and H-1 NMR spectroscopy. Solid state structural studies carried out using small angle X-ray scattering and wide angle X-ray diffraction experiments revealed altered packing of the D and A molecules in the complexes. Transmission electron microscopy images showed lamellar structures in the <10 nm scale for the P4VP(OPV1.00), P4VP(UPBI1.00), and mixed P4VP (D-A) complexes. The effect of the nanoscopic D-A self-assembly on the bulk mobility of the materials was probed using SCLC measurements. The mixed D-A random complexes exhibited ambipolar charge transport characteristics with higher values for the average bulk hole mobility estimate. P4VP(OPV0.25+UPBI0.75) exhibited an average hole mobility in the order of 10(-2) cm(2) V-1 s(-1) and electron mobility 10(-5) cm(2) V-1 s(-1). (C) 2016 Wiley Periodicals, Inc.
Keywords: donor-acceptor; oligo(phenylenevinylene); P4VP; Perylenebisimide; Self-assembly; structure-property relations; supramolecular comb polymer; supramolecular structures

Selenium-containing fused bicyclic heterocycle diselenolodiselenole: field effect transistorstudy and structure property relationship - Debnath, Sashi; Chithiravel, Sundaresan; Sharma, Sagar; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (ACS Applied Materials & Interfaces, 2016)
The first application of the diselenolodiselenole (C4Se4) heterocycle as an active organic field effect transistor materials is demonstrated here. C4Se4 derivatives (2a-2d) were obtained by using a newly developed straightforward diselenocyclization protocol, which includes the reaction of diynes with selenium powder at elevated temperature. C4Se4 derivatives exhibit strong donor characteristics and planar structure (except 2d). The atomic force microscopic analysis and thin-film X-ray diffraction pattern of compounds 2a-2d indicated the formation of distinct crystalline films that contain large domains. A scanning electron microscopy study of compound 2b showed development of symmetrical grains with an average diameter of 150 nm. Interestingly, 2b exhibited superior hole mobility, approaching 0.027 cm(2) V-1 s(-1) with a transconductance of 9.2 mu S. This study correlate the effect of p-stacking, Se center dot center dot center dot Se intermolecular interaction, and planarity with the charge transport properties and performance in the field effect transistor devices. We have shown that the planarity in C4Se4 derivatives was achieved by varying the end groups attached to the C4Se4 core. In turn, optoelectronic properties can also be tuned for all these derivatives by end-group variation.

Dihedral angle control to improve the charge transport properties of conjugated polymers in organic field effect transistors - Dharmapurikar, Satej S.; Chithiravel, Sundaresan; Mane, Manoj V.; Deshmukh, Gunvant; Krishnamoorthy, Kothandam (Chemical Physics Letters, 2018)
Diketopyrrolopyrrole (DPP) and i-Indigo (i-Ind) are two monomers that are widely explored as active materials in organic field effect transistor and solar cells. These two molecules showed impressive charge carrier mobility due to better packing that are facilitated by quadrupoles. We hypothesized that the copolymers of these monomers would also exhibit high charge carrier mobility. However, we envisioned that the dihedral angle at the connecting point between the monomers will play a crucial role in packing as well as charge transport. To understand the impact of dihedral angle on charge transport, we synthesized three copolymers, wherein the DPP was sandwiched between benzenes, thiophenes and furans. The copolymer of i-Indigo and furan comprising DPP showed a band gap of 1.4 eV with a very high dihedral angle of 179 degrees. The polymer was found to pack better and the coherence length was found to be 112 angstrom. The hole carrier mobility of these polymer was found to be highest among the synthesized polymer i. e. 0.01 cm(2)/vs. The copolymer comprising benzene did not transport hole and electrons. The dihedral angle at the connecting point between i and Indigo and benzene DPP was 143 angstrom, which the packing and consequently charge transport properties. (C) 2018 Elsevier B. V. All rights reserved.

Experimental and theoretical investigations of different diketopyrrolopyrrole-based polymers - Murugan, Pachaiyappan; Raghavendra, Venkatraman.; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Mandal, Asit Baran; Subramanian, Venkatesan; Samanta, Debasis (ACS Omega, 2018)
Diketopyrrolopyrrole (DPP)-based polymers are often considered las the most promising donor moiety in traditional bulk heterojunction solar cell devices. In this paper, we report the synthesis, characterization of various DPP-based copolymers with different molecular weights, l and polydisper sity where other aromatic repeating units (phenyl or thiophene based) are connected by alternate double bonds or triple bonds. Some of the copolymers were used for device fabrication and the crucial parameters such as fill factor (FF) and open circuit voltage (V-oc) were calculated. The density functional theory was used to optimize the geometries and deduce highest occupied molecular orbital lowest unoccupied molecular orbital gaps of all the polymers and'theoretically predict their optical and electronic properties. Optical properties of all the polymers, electrochemical properties and band gaps were also obtained experimentally and compared with the theoretically predicted values.